Low-cost solution-processed copper iodide as an alternative to PEDOT:PSS hole transport layer for efficient and stable inverted planar heterojunction perovskite solar cells1. Issue 38 (14th October 2015) - Chen, Wei-Yi; Deng, Lin-Long; Dai, Si-Min; Wang, Xin; Tian, Cheng-Bo; Zhan, Xin-Xing; Xie, Su-Yuan; Huang, Rong-Bin; Zheng, Lan-Sun
<x xml:space="preserve">Abstract</x> Low-cost solution-processed copper iodide replaces PEDOT:PSS in inverted planar heterojunction perovskite solar cells with high efficiency and enhanced stability.